Development Strategy of the Minapolitan Area in East Sei Kepayang District, Asahan Regency - Dedy Armansyah; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study aims to examine the Development Strategy of the Minapolitan Area in East Sei Kepayang District,Asahan Regency. The qualitative approach is used because this research aims to dig deeper into the perceptions,views, and experiences of various related parties, including local communities, stakeholders, Data is collectedthrough various relevant qualitative methods, including: In-depth Interview An in-depth interview is conductedto obtain the views, experiences, and perspectives of the main actors involved in regional developmentMinapolitan. To ensure the validity of the data, data triangulation is used, which is comparing and confirmingdata from various sources (interviews, observations, and documentation). Research Results The developmentand improvement of fisheries infrastructure, including road access, cold storage facilities, and fish processingcenters, is an important step to improve distribution efficiency, maintain product quality, and add added valueto fishery products. Strategies to increase access to financing and attract private investment are importantelements in overcoming capital constraints. The adoption of modern fisheries technology, both in aquacultureand capture fisheries, is a strategic step that will increase productivity and preserve natural resources.Sustainable management of natural resources, including efforts to preserve aquatic ecosystems and preventpollution, is an important foundation in ensuring the long-term availability of fish.